2003
DOI: 10.1038/sj.npp.1300172
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of the Interleukin-1beta (C-511T) Genetic Polymorphism with Major Depressive Disorder, Associated Symptomatology, and Antidepressant Response

Abstract: Proinflammatory cytokines, including interleukin (IL)-1beta, are suggested to have a role in the pathogenesis of major depressive disorder (MDD) and be related to the therapeutic effects of antidepressants. To elucidate a genetic predisposition of MDD, we studied biallelic polymorphism in the promoter region (position -511) of the IL-1beta gene in 157 patients with MDD and in 112 controls. We also examined the association of this polymorphism and fluoxetine therapeutic response in 119 MDD patients who received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
3
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 24 publications
9
71
3
2
Order By: Relevance
“…The G allele of the rs16944 polymorphism (located within the promoter of the IL-1b gene) has been associated with SSRI non-response (Yu et al 2003;Tadic et al 2008;Baune et al 2010) and with recurrent major depression (Borkowska et al 2011). In addition, IL-1b promoter polymorphism rs1143627 was also associated with recurrent major depression (Borkowska et al 2011).…”
Section: Genetic Polymorphismsmentioning
confidence: 99%
“…The G allele of the rs16944 polymorphism (located within the promoter of the IL-1b gene) has been associated with SSRI non-response (Yu et al 2003;Tadic et al 2008;Baune et al 2010) and with recurrent major depression (Borkowska et al 2011). In addition, IL-1b promoter polymorphism rs1143627 was also associated with recurrent major depression (Borkowska et al 2011).…”
Section: Genetic Polymorphismsmentioning
confidence: 99%
“…Furthermore, a recent study among 74 depressed patients found that expression of genes related to inflammation predicted non-response to a 8-week treatment with escitalopram or nortriptyline (Cattaneo et al, 2013). Lastly, the IL-1b gene (C-511T, rs19644 and rs1143643) has been shown to predict antidepressant non-response (Baune et al, 2010;Yu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 (4) Genetic association between genes of inflammatory factors, including polymorphisms in IL-1 family genes, and severity of depression and its responsiveness to antidepressant treatment. 12 (5) Cytokine-related induction of depressed mood in normal subjects following experimental exposure to immune challenges. [13][14][15] (6) Studies in experimental animals, showing that exposure to various immune challenges, as well as exogenous administration of IL-1, either peripherally or directly into the brain, produce depressive-like symptoms, which can be attenuated by chronic treatment with antidepressant drugs, 1,[16][17][18][19] as well as by pretreatment with cytokine antagonists, particularly IL-1ra, and by manipulations in IL-1 family genes.…”
Section: Introductionmentioning
confidence: 99%